Association between life conditions and vulnerability with mortality from cardiovascular diseases in elderly men of Northeast Brazil - Jozemar Pereira dos Santos; Neir Antunes Paes (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
The study aimed at identifying explanatory factors of the mortality rate of elderly men due to cardiovascular diseases in the 187 micro regions of Northeast Brazil, in 2000, based on indicators of life conditions and vulnerability of that population, using the structural equations modeling. The following methodological steps were taken: (1) using Censo 2000's microdata, 10 indicators were selected to the latent exogenous construct 'life conditions and vulnerability'. Using the Information System of Mortality from the Brazilian Ministry of Health, data about deaths from the four major basic causes of cardiovascular diseases were collected, which composed the endogenous latent construct as the outcome variable; (2) qualitative analysis of mortality data; (3) statistical analysis using the structural equation modeling through two phases: adjustment of the outcome variables measurement model and adjustment of the obtained structural model. Due to the multicollinearity observed, three indicators showed significance for the measurement model: years of study, percentage of elderly men in households with bathroom/plumbing and survival probability at 60 years of age. The structural model indicated adjustment adequacy of the model, which the measurement of standardized coefficient was considered of strong effect (SC = 0.81, p-value < 0.01) and coefficient of determination r2 = 66%. It was concluded that indicators of life conditions and vulnerability were highly associated with the mortality rate from cardiovascular diseases in elderly men from Northeast Brazil in 2000.